Named cells and inclusion bodies in bacterial and viral infections associated with oral cavity - Dhume, Manjeeta S. M.; Dias, Clarence P. (International Journal of Research in Medical Sciences, 2023)
An oral pathologist can explore the world of intricate features in complicated tissues thanks to this visual speciality. Because our eyes are more accustomed to seeing normal morphology in cells and structures, we can become stuck in a state of flux when we encounter specific ill cells or bodies. Although they may appear to be deceiving, they aid the pathologist in making a diagnosis because they are pathognomonic for numerous diseases and conditions. With a focus on pathogenesis, microscopic features, and stains used to highlight features of the same, the current article is an attempt to compile various histopathological bodies seen in various diseases associated with bacterial and viral diseases associated with the oral cavity.